Acute thrombotic occlusion of subclavian artery presenting as a stroke mimic - Ankur Verma; Sanjay Jaiswal; Wasil Rasool Sheikh (Journal of the American College of Emergency Physicians Open)
Abstract It has been well established and widely accepted that thrombolysis using recombinant tissue plasminogen activator (rTPA) is strongly beneficial for acute stroke patients. The sensitivity of brain tissue to ischemia causes this time dependence of the effectiveness of rTPA. Early recognition and management of a stroke is imperative for positive outcomes in such patients. Clinical assessment warrants immediate treatment for patients with suspected stroke. As emergency physicians, an awareness of stroke mimics who might undergo unwarranted investigations and thrombolysis is important. We present a case of an elderly female who presented with sudden onset of left upper limb weakness, was thrombolysed and was subsequently diagnosed with subclavian artery thrombotic occlusion. Acute limb ischemia is a rare cause of a stroke mimic. It would be prudent for emergency physicians to be aware regarding the same, especially in patients presenting with monoplegia.